Does Institutional Ownership Contribute to Decarbonization Strategies? Empirical Studies in Emerging Markets - Zayyan Ahmad Nuryaddin; Novrys Suhardianto (Jurnal Reviu Akuntansi dan Keuangan, 2025)
Purpose: This study aims to examine the relationship between institutional ownership and greenhouse gas (GHG) emissions. Methodology/approach: The research sample consists of 182 companies listed on the Indonesia Stock Exchange (IDX) during the period 2018–2022, with data collected from Bloomberg and Osiris databases. The analysis was conducted using the Ordinary Least Squares (OLS) method with STATA 17 software. Findings: The results indicate that institutional ownership has a negative and significant association on total GHG emissions, particularly on Scope 1 emissions. However, the association of institutional ownership on indirect emissions (Scope 2 and 3) is not statistically significant. Practical and Theoretical contribution/Originality: This study contributes by providing empirical evidence that institutional investors are more effective in reducing direct emissions, while their influence on supply chain and energy consumption-related emissions remains limited. The findings offer valuable insights for companies in enhancing transparency and improving their carbon emission management strategies. Research Limitation: This study is limited to Indonesian firms over a specific period. Future research should include more countries, a longer timeframe, and additional variables like renewable energy policies and government incentives for broader insights.